USING MIND MAPPING TO IMPROVE ARGUMENTATIVE WRITING SCORE OF ELEVENTH GRADERS - Daniel O'Hara; Bartolomeus Budiyono (Magister Scientiae, 2019)
This study used a classroom action research design. It aimed at identifying the improvement of argumentative essay scores of eleventh graders of Elyon Christian School Surabaya in the 2013/2014 academic year through mind mapping. Besides that, it was also conducted to describe the process of teaching writing using mind mapping to the eleventh graders. The data was obtained by giving pre-test, cycle process and post-test. The result showed that there were improvements in the students‘ argumentative essay scores. It can be seen at the average scores of the pre-test (62. 5) and post-test (85. 5). The research process took six weeks for completion, or twelve classroom meetings. It was also found that the students followed the teaching-learning process well and they showed their interest in the lesson. Based on the analysis, it was concluded that the eleventh graders of Elyon Christian School Surabaya improved their argumentative essay writing score through the mind mapping technique.